RETRACTED: Boyer-Moore String Matching Algorithm and SHA512 Implementation for Jpeg/exif File Fingerprint Compilation in DSA - Fitriyanto, Rachmad; Yudhana, Anton; Sunardi, Sunardi (Universitas Negeri Semarang, 2020)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).Similar article has appeared inÂ http://jurnalnasional.ump.ac.id/index.php/JUITA/article/view/4413